Dual-function water-level/well-depth meter. (February 2020) - Rashed, Mohamed
Highlights: Water-Level/Well-Depth meter is a newly designed dual-function well sounder. It measures both depth to water level and depth to well bottom using a single probe. Intensive quality check indicates its efficiency, precision and durability. Field tests show that it requires less time and effort than available sounders. Detailed parts description and dimensions and manufacturing methods are provided. Abstract: Depth to water table and depth to well bottom are crucial measurements for hydrological and hydrogeological investigations. Available water level meters, commonly called well sounders, measure only depth to water table. For depth to well bottom, hydrogeologists hustle to sense when the sounder tip touches the well bottom to get a rough estimation of the depth to well bottom. This introduces significant amount of error and is extremely hard to apply in deep wells. Some recently introduced sounders have a special probe for measuring well bottom depth. However, those sounders are tedious to use and lack the required durability because of the need to roll up the entire cable and to swap probes for every measurement. Water-Level/Well-Depth (WL/WD) meter is novel dual-function well sounder that is capable of measuring both water table level and depth to well bottom using a single probe easily and precisely. The sounder probe is designed in a way that allows sensing both water table and depth to well bottom efficiently. The reel, cable and electronic circuit are also modified in a way that allows for switching between water level and well bottom depth measurements with a push of a button. Field tests conducted on the new WL/WB meter clearly show its efficiency, precision and durability.